2021
DOI: 10.1016/j.scs.2021.103046
|View full text |Cite
|
Sign up to set email alerts
|

Role of different types of nanomaterials against diagnosis, prevention and therapy of COVID-19

Abstract: Graphical Abstracts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 274 publications
(342 reference statements)
0
22
0
Order By: Relevance
“…The potential and different alternatives have been evaluated for the use of breath sensor technology in monitoring critically ill and COVID-19 patients. In fact, different types of nanomaterials have attracted the attention of the scientists in diagnosis, detection, monitoring, and therapy applications against COVID-19 [ 26 ]. Looking at the pathophysiology of COVID-19, there are several indicators that a coronavirus infection is detectable in the breath VOC pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The potential and different alternatives have been evaluated for the use of breath sensor technology in monitoring critically ill and COVID-19 patients. In fact, different types of nanomaterials have attracted the attention of the scientists in diagnosis, detection, monitoring, and therapy applications against COVID-19 [ 26 ]. Looking at the pathophysiology of COVID-19, there are several indicators that a coronavirus infection is detectable in the breath VOC pattern.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, damaged cell membrane (coenzyme A) disturbed the cellular respiration, other biochemical systems, and ultimately cause cell lysis ( Ghotekar et al, 2021 ; Bandala et al, 2021 ). Depending upon the complexity of the virus structure, the comprehensive degradation mechanism involves; (a) the peroxidation of proteins, lipids by radicles that depresses the periplasmic enzyme activity and damage the genetic RNA material; (b) release of metal ions (photocatalyst) into the cell that interacts with COOH, –NH, –SH like functional groups to damage nucleic acids; and (c) disturbing the cellular metabolism without the induction of oxidative stress ( Li et al, 2020a ; Ghaemi et al, 2021 ). Thus, understanding the deactivation mechanism of viruses might be helpful to construct more superior potential photocatalytic materials with apt morphology and practical importance.…”
Section: Photocatalytic Performance Evaluation On Virus Disinfectionmentioning
confidence: 99%
“…In this case, lipidic formulations and polymeric nanoparticles can be used as carriers, as their size, morphology and charge are tailored according the particular situation [ 251 , 252 , 253 , 254 , 255 , 256 ]. In a very recent review, Ghaemi et al [ 257 ] highlighted the most used nanomaterials/nanoparticles with high potential in therapy, prevention and detection of targeted virus proteins: carbon nanotubes, graphene and graphene oxide, fullerene, quantum dots, CuNPs, ZnNPs, AgNPs, TiO 2 and chitosan NPs. They concluded that the inclusion of nanomaterials in biosensors offer more detection capability, stability, simplicity of design, reliability and affordability.…”
Section: Metal Nanoparticles and Carbon-based Nanomaterials In (Bio)sensors Designmentioning
confidence: 99%
“…The antigen lateral flow detection of SARS-CoV-2 as a point-of-care approach is realized by using a membrane strip with two lines: first line for the antibody-Au NPs, and second line for the captured antibodies. Biological samples such as blood or urine samples can be applied on the membrane, while, based on the capillary mechanism, proteins are drawn across the strip and an antigen/antibody AuNPs complex is formed and immobilized, a pair of red or blue lines becoming evident [ 257 , 264 ].…”
Section: Metal Nanoparticles and Carbon-based Nanomaterials In (Bio)sensors Designmentioning
confidence: 99%